Geological correlation of Neves-Corvo Mine and Pomarão Antiform sequences (Iberian Pyrite Belt, Portugal) - Albardeiro, Luís (2021)
ABSTRACT: A geological correlation between Neves-Corvo (NC) and Pomarão antiforms is attempted. These regional scale major sequences are easily correlated but, at local scale, facies and age differences stand out. Stratigraphy includes: i) the Phyllite-Quartzite Group with identical paleogeography setting and similar late Famennian ages for uppermost levels (LL to LN miospore biozones in Pomarão and NC respectively). ii) the Volcano-Sedimentary Complex shows some discrepancy concerning the age distribution of the felsic volcanic rocks (ca. 356-330 for Pomarão and ca. 365-346 Ma for all NC area) while sediments range from mid-Famennian to late Visean age (VH to NM Miospore Biozone for NC). iii); the Baixo Alentejo Flysch Group (late Visean NM Miospore Biozone onwards in NC), covering the previous sequences and being slightly older than the uppermost volcanic rocks of Pomarão. The correlation between these two structures is supported by geology and isotopic/biozone ages and favours exploration scenarios in both regions.